Is air transport of stroke patients faster than ground transport? A prospective controlled observational study. Issue 4 (6th February 2013) - Hesselfeldt, Rasmus; Gyllenborg, Jesper; Steinmetz, Jacob; Do, Hien Quoc; Hejselbæk, Julie; Rasmussen, Lars S
Abstract : Background: Helicopters are widely used for interhospital transfers of stroke patients, but the benefit is sparsely documented. We hypothesised that helicopter transport would reduce system delay to thrombolytic treatment at the regional stroke centre. Methods: In this prospective controlled observational study, we included patients referred to a stroke centre if their ground transport time exceeded 30 min, or they were transported by a secondarily dispatched, physician-staffed helicopter. The primary endpoint was time from telephone contact to triaging neurologist to arrival in the stroke centre. Secondary endpoints included modified Rankin Scale at 3 months, 30-day and 1-year mortality. Results: A total of 330 patients were included; 265 with ground transport and 65 with helicopter, of which 87 (33%) and 22 (34%), received thrombolysis, respectively (p=0.88). Time from contact to triaging neurologist to arrival in the regional stroke centre was significantly shorter in the ground group (55 (34–85) vs 68 (40–85) min, p<0.01). The distance from scene to stroke centre was shorter in the ground group (67 (42–136) km) than in the helicopter group (83 (46–143) km) (p<0.01). We did not detect significant differences in modified Rankin Scale at 3 months, in 30-day (9.4% vs 0%; p=0.20) nor 1-year (18.8% vs 13.6%; p=0.76) mortality between ground and helicopter transport. Conclusions: We found significantly shorter time from contact to triaging neurologist to arrival in the regional stroke centre if stroke patients were transported by primarily dispatched ground ambulance compared with a secondarily dispatched helicopter.